PENGARUH IKLIM ORGANISASI, KOMPENSASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT TOTAL E&P INDONESIE CABANG KOTA BALIKPAPAN - NOVI INDIANI; TETRA HIDAYATI; SITI MARIA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
Organizational Climate, Compensation and Organizatinal Commitment is one of several factors that affect to the Performance of employee. This story aims to    examine    and    analyze    Organizational    Climate,    Compensation    and Organizational  Commitment  to  the  performance  of  PT.  Total  EP  Indonesie employee branch of Balikpapan City. This research conducted using multiplelinear regression called SPSS version 20 in analyzing the data. Hypothesis testing result show that Organization Climatte, Compensation, and Organizational Commitment has a positive and significant impact on the Performance of PT. Total EP Indonesie employee branch of Balikpapan City.Keywords: Organizational Climate, Compensation, Organizational Commitment and Employee Performance.